Nie trzeba glosno mowic : powiesc - Mackiewicz, Jozef (Londyn : Kontra, 1985)
A novel recounting the terrible days of World War II. A sequel to Droga donikad.
Reprint. First published: London : Kontra, 1980.
Includes bibliographical references (p. 549-551) and index.
Keywords: World War, 1939-1945 -- Fiction; Historical fiction, Polish